Elicitation of health state utilities associated with differing durations of morning stiffness in rheumatoid arthritis. - Iqbal, I; Dasgupta, B; Taylor, P; Heron, L; Pilling, C (2012)
OBJECTIVE: Specific symptoms of rheumatoid arthritis (RA), including joint stiffness and functional disability, are most severe in the morning. 'Morning stiffness' has a negative impact on health-related quality-of-life (HRQoL); however, how HRQoL is correlated to morning stiffness duration is unknown. The objective of this study was to obtain population-based utility values associated with different durations of morning stiffness in RA. DESIGN AND METHODS: The time-trade-off (TTO) approach was used to elicit utility values for four different health states (HS), which differed in morning stiffness duration. One hundred and nine members of the UK general public rated each HS in individual face-to-face interviews with trained investigators. TTO scores were converted into utility values. Visual Analog Scale (VAS) scores were obtained to validate TTO scores. RESULTS: On a scale of 0 (death) to 1 (full health), a mean utility value of 0.45±0.29 was elicited for ∼3 h of morning stiffness (anchor HS), 0.50±0.28 for 2-3 h of morning stiffness (HS1), 0.61±0.25 for 1-2 h of morning stiffness (HS2) and 0.78±0.20 for <1 h of morning stiffness (HS3). The difference between each HS was statistically significant (p<0.01). Mean VAS utility scores followed the same trend. Utility incrementally increased with each HS associated with a shorter duration of morning stiffness. Limitations of this research include potential bias from the TTO method due to the discounting effect of time, scale compatibility, and loss aversion. CONCLUSIONS: The UK population-based utility values show a reduction in morning stiffness duration in RA is associated with improved HRQoL. Despite the impact of morning stiffness on HRQoL, it is rarely evaluated and little is known as to how it is affected by current treatments. The results of this study can be applied in future cost-utility analyses of healthcare interventions which target an improvement in morning stiffness duration for RA patients.